Biomechanical coordination and variability alters following repetitive movement fatigue in overhead athletes with painful shoulder - Rahman Sheikhhoseini; Sajjad Abdollahi; Mohammad Salsali; Mehrdad Anbarian (Scientific Reports)
Abstract Most sports and leisure activities involve repetitive movements in the upper limb, which are typically linked to pain and discomfort in the neck and shoulder area. Movement variability is generally expressed by changes in movement parameters from one movement to another and is a time-dependent feature of repetitive activities. The purpose of this study was to examine the effect of repeated movement-induced fatigue on biomechanical coordination and variability in athletes with and without chronic shoulder pain (CSP). In this controlled laboratory study, 24 overhead athletes in two groups of athletes with (N = 12) and without (N = 12) CSP were recruited. Biomechanical and Electromyographical data were recorded while the athletes were asked to perform repeating reaching tasks (RRT). Kinematic data was recorded every 30 s of the minutes of the repetitive pointing task (RPT). The kinematic and electromyography data were recorded at the first 30 s of “Fatigue-Terminal” (FT) and the last 30 s of “No-Fatigue” (NF) in the repetitive pointing task (RPT). Raw data was analyzed by using MATLAB code to extract the relevant coordination and movement variability data. Different fatigue conditions led to significant kinematic changes during the repetitive pointing task. In the CSP group, trunk lateral flexion decreased after fatigue, while it increased in the CON group (p < 0.013). Trunk rotation and shoulder elevation angles were smaller before fatigue than after in both groups (p < 0.001). Variability in joint angles, including trunk lateral flexion and elbow flexion, increased after fatigue, indicating less stability in movement patterns (p < 0.001). The coordination between trunk movement and shoulder elevation was altered post-fatigue, with significant changes in EMG variability for muscles like the Lower Trapezius and Long Head of the Biceps (p < 0.001). Results of our study indicate that both groups were able to accomplish fatigue, but they employed different movement strategies. The CSP group primarily focused on controlling the shoulder joint, while the CON group utilized both the shoulder and elbow joints in their strategy. This difference suggests that individuals in the CSP group who experienced chronic pain may have developed a strategy to minimize pain and fatigue during the task. Specifically, the CSP group’s approach appeared to involve adjustments in movement patterns to manage the task despite fatigue. This adaptation contrasts with the CON group’s more complex movement strategy, which involved greater variability and adjustments in both the shoulder and elbow joints.